The Effects of Tocilizumab in Patients with Active Thyroid Eye Disease Refractory to Corticosteroids - Pedro Filipe Braga Barbosa Lopes Moás (2022)
Introduction: Thyroid eye disease (TED) is an autoimmune condition related to the production of pro-inflammatory cytokines, such as interleukin-6, that causes enlargement of extraocular muscles and retrobulbar fat, leading to restriction of the eye movements, exophthalmos, and diplopia. The assessment of TED relies on the clinical activity score (CAS). Tocilizumab is an alternative treatment to TED. Aim: Assess the efficacy of TCZ as well as the occurrence of side effects in reducing the activity of TED in patients refractory to corticotherapy (GC) regimen. Methods: Seven patients presented active TED (CAS ≥ 4). We evaluated them before receiving GC treatment, before starting TCZ treatment and after finishing TCZ treatment (post-TCZ) for CAS and thyroid function (Thyroid Stimulating Hormone (TSH), Free Thyroxine (FT4) and TSH Receptor Antibodies (TRAbs)). Results: 3 males and 4 females with a median age of 52 [46-55] years were enrolled in the study. All of them presented a non-active TED post-TCZ. Median TRAbs before treatment with TCZ was 23.30 [1.90-40.00] and after treatment was 1.80 [1.50-4.40]. TRAbs decreased after TCZ treatment (p < 0.043). No other differences were found. Discussion: TCZ is an effective alternative to treat safely TED as it has proved to be effective and safe in reducing symptoms.